Sr Examen

Expresión yx∨zx∨!yzx

El profesor se sorprenderá mucho al ver tu solución correcta😉

    Solución

    Ha introducido [src]
    (x∧y)∨(x∧z)∨(x∧z∧(¬y))
    (xy)(xz)(xz¬y)\left(x \wedge y\right) \vee \left(x \wedge z\right) \vee \left(x \wedge z \wedge \neg y\right)
    Solución detallada
    (xy)(xz)(xz¬y)=x(yz)\left(x \wedge y\right) \vee \left(x \wedge z\right) \vee \left(x \wedge z \wedge \neg y\right) = x \wedge \left(y \vee z\right)
    Simplificación [src]
    x(yz)x \wedge \left(y \vee z\right)
    x∧(y∨z)
    Tabla de verdad
    +---+---+---+--------+
    | x | y | z | result |
    +===+===+===+========+
    | 0 | 0 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 0 | 1 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 1 | 0      |
    +---+---+---+--------+
    | 1 | 0 | 0 | 0      |
    +---+---+---+--------+
    | 1 | 0 | 1 | 1      |
    +---+---+---+--------+
    | 1 | 1 | 0 | 1      |
    +---+---+---+--------+
    | 1 | 1 | 1 | 1      |
    +---+---+---+--------+
    FNCD [src]
    x(yz)x \wedge \left(y \vee z\right)
    x∧(y∨z)
    FNDP [src]
    (xy)(xz)\left(x \wedge y\right) \vee \left(x \wedge z\right)
    (x∧y)∨(x∧z)
    FNC [src]
    Ya está reducido a FNC
    x(yz)x \wedge \left(y \vee z\right)
    x∧(y∨z)
    FND [src]
    (xy)(xz)\left(x \wedge y\right) \vee \left(x \wedge z\right)
    (x∧y)∨(x∧z)